Problem-Based Learning Management System (PBLMS): A Mobile Learning Application to Facilitate Creative Thinking Skills (CTS) of Prospective Physics Teachers - Rizal, Rahmat; Surahman, Endang; Aripin, Haji; Maulidah, Rifa'atul (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Creative thinking is a 21st-century skill that lecturers should facilitate since the current challenge and conditions are getting more complex. These skills can be facilitated using technology through mobile learning using Problem-Based Learning Management System (PBLMS). This study aimed to obtain an overview of the improvement in the creative thinking skills of prospective physics teachers after participating in mobile learning using PBLMS. This is a quasi-experimental study with a non-equivalent control group design. The population of this study consisted of 80 first-year students at a university in Tasikmalaya. The sample consisted of 50 students who were selected using purposive sampling. They were 16 men and 34 women with an age range of 19–21 years. The data were collected using tests, observations, and interviews. The instruments used in this study included Creative Thinking Skill (CTS) tests, that is, the sheets of learning process observation, and interview guidance. The enhancement of CTS was processed using normalized gain and strengthened statistically by two mean difference tests. The group that took lectures using PBLMS had a higher score with an N-Gain of 0.72 (high category), while the group without PBLMS had an N-gain of 0.61 (medium category). Statistically, the two mean difference tests showed that the significance obtained was 0.003, so it can be concluded that there was a significant difference between the groups using PBLMS and without PBLMS. The research can provide an overview of the usefulness of PBLMS in supporting the achievement of learning objectives and other related skills.